Strategies for sustainable mangrove ecotourism development in Lembung, Pamekasan - islam, Darul; Lutfia, Citra; Wijayani, Qoni’ah Nur (Jurnal Ilmu Manajemen, 2025)
Tourism is a key sector that contributes significantly to regional economic growth and national development, particularly as a source of foreign exchange. This sector generates income by utilising the beauty of nature and cultural diversity without directly exploiting natural resources. However, the rapid growth of tourism often leads to challenges such as environmental degradation, ecosystem disruption, and unsustainable tourist behaviour. Ecotourism has emerged as an alternative model for sustainable tourism development, emphasising environmental conservation, local community empowerment, and the preservation of socio-cultural values. Mangrove forests hold great potential for Ecotourism due to their critical ecological functions and economic value if managed wisely. Sustainable tourism is essential for mangrove ecotourism development, focusing on maximising positive impacts while minimising negative ones on the environment, culture, and local communities. This study aims to identify ecotourism practices in the mangrove area of Lembung Village, Pamekasan, and formulate strategic concepts for sustainable ecotourism management based on the local economy. A qualitative descriptive approach was employed, involving stakeholders such as ecotourism managers, village officials, local entrepreneurs, community members, and tourists. The results of this study are expected to serve as a reference for developing integrated mangrove ecotourism that balances environmental conservation, community empowerment, and the preservation of local cultural heritage in a sustainable manner. These insights contribute to the literature on community-based Ecotourism and offer practical guidance for sustainable mangrove tourism management. The results of the SWOT analysis indicate an aggressive strategy that focuses on utilising internal strengths and external opportunities, including the establishment of BUMDes and cooperatives as the management institutional framework